Introduction of heat and energy-saving structures in construction as a condition of its sustainable ecological and economic development (Academic journal Industrial Machine Building Civil Engineering, 2022)
The article identifies the main aspects of sustainable construction development in the implementation of the development strategy. Approaches and proposals for interrelated components of improving the efficiency of construction production, which are based on interdependent and complementary actions to achieve the competitiveness of the construction industry and are relevant to the functioning of the construction industry. Directions for improving construction production through the introduction of heat-saving structures at construction sites are proposed. The conclusions analyze the results of the construction industry. It is determined that the use of heat-saving structures, technologies, the formation and implementation on this basis of a strategy of long-term sustainable development - one of the construction priorities.
Keywords: sustainable development; construction production; heat-saving structures